Desenvolvimento de uma base de dados nacional para um instrumento automatizado de medidas do campo visual in vivo - Carvalho, Valéria Mellaci de (2013)
Glaucoma is a leading cause of blindness in the elderly throughout the world. One of the most important diagnoses that is made in order to detect this pathology is a visual field perimetry, which measures the sensitivity of different portions of the retina to different light intensities. However, the available instruments in Brazil with quality considered within the "Gold Standard" are all imported and therefore the basis of all computational data, information essential to obtain a reliable report is also based on populations with ethnic and demographic characteristics distinct from the Brazilian population. In this project, the goal was to develop a database with emphasis on the Brazilian population for a computerized instrument that performs measurements of the visual field of the human eye. Practical results of this new database are presented and also a discussion of why it is more appropriate for the Brazilian population when compared to imported databases.